Dose Effects of Histone Deacetylase Inhibitor Tacedinaline (CI-994) on Antipsychotic Haloperidol-Induced Motor and Memory Side Effects in Aged Mice - McClarty, Bryan; Rodriguez, Guadalupe; Dong, Hongxin (Frontiers in Neuroscience, 2021)
Background: Elderly patients treated with antipsychotic drugs often experience increased severity and frequency of side effects, yet the mechanisms are not well understood. Studies from our group indicate age-related histone modifications at drug targeted receptor gene promoters may contribute to the increased side effects, and histone deacetylase (HDAC) inhibitors MS-275 and VPA could reverse typical antipsychotic haloperidol (HAL) induced motor-side effects. However, whether such effects could be dose dependent and HDAC inhibitors could improve memory function in aged mice is unknown. Methods:We co-treated selective class 1 HDAC inhibitor tacedinaline (CI-994) at different doses (10, 20 and 30 mg/kg) with HAL (0.05mg/kg) in young (3 months) and aged (21 months) mice for 14 consecutive days, then motor and memory behavioral tests were conducted, followed by biochemical measurements. Results:CI-994 at doses of 10 and 20 mg/kg could decrease HAL-induced cataleptic episodes but only 20 mg/kg was sufficient to improve motor coordination in aged mice. Additionally, CI-994 at 10 and 20 mg/kg mitigate HAL-induced memory impairment in aged mice. Biochemical analyses showed increased acetylation of histone marks H3K27ac and H3K18ac at the dopamine 2 receptor (D2R) gene (Drd2) promoter and increased expression of the D2R in the striatum of aged mice after administration of CI-994 at 20 mg/kg. Conclusions:Our results suggest CI-994 can reduce HAL-induced motor and memory side effects in aged mice. These effects may act through an increase of acetylation at the Drd2 promoter, thereby restoring D2R expression and improving antipsychotic drug action.